FROM TASTE TO RECOMMENDATION: THE INFLUENCE OF GASTRONOMIC MOTIVATION AND ONLINE BEHAVIOUR ON TOURISTS’ eWOM IN VOJVODINA - Vukolić, Dragan; Gajić, Tamara; Milošević, Srđan (The Business of Tourism, 2025)
The aim of this study is to examine the role of gastronomic offerings as a factor that enhances the visibility of tourist destinations through electronic word-of-mouth (eWOM), with a particular focus on gastronomic events in Vojvodina. Gastronomy is increasingly recognised as a significant motive for tourist arrivals, especially in regional and rural destinations where the authenticity of local cuisine represents added value within the tourism offer. The study employed a quantitative approach through a survey questionnaire conducted among tourists who participated in selected gastronomic events in Vojvodina. Motivational factors, the level of satisfaction with the gastronomic experience, and tourists’ willingness to share their impressions via social networks and online platforms were analysed. The results indicate a positive correlation between the quality of gastronomic offerings and the intention to engage in eWOM, implying that gastronomic events can significantly contribute to the digital promotion of destinations. Based on the findings, recommendations have been formulated to improve gastronomic offerings as a tool for sustainable tourism development and for strengthening Vojvodina’s position on the tourism map through modern communication channels.
Keywords: gastronomic tourism; eWom; tourist motivation; Vojvodina; gastronomic events; digital promotion